Metabolic demands of different apparatus routines between elite and sub-elite rhythmic gymnasts - Douda, H.; Avloniti, A.; Maridaki, M.; Tokmakidis, S. P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Rhythmic Gymnastics (RG) routines compose an aesthetic collage of movements including steps, leaps, balances, turns and flexibility within the time limit of 90 sec. Gymnasts perform the above elements accented by music and execute them with elegance, expression and controlled amplitude. All of the above must be coordinated separately with the different characteristic movements of each apparatus (rope, hoop, ball, ribbon, clubs). Because of these specific difficulties, there has been very little research conducted on the metabolic demands of RG routines (Alexander et al., 1987; Imhof, 1986; Guidetti et al., 2000). The purpose of this study was to determine the metabolic demands using the measurement of oxygen consumption, heart rate responses and lactate concentration during RG routines on different apparatus between elite and sub-elite athletes. Methods: Forty-six gymnasts, age 12.42±2.06 yrs, height 148.83±9.84 cm, weight 35.26±6.53 kg, body fat 14.13±2.64 % and training age 6.01±2.21 yrs, divided into two groups (elite: n=19, sub-elite: n=27) and performed an incremental laboratory exercise test on a cycle-ergometer up to exhaustion. Energy demands were assessed with direct field measurements of oxygen uptake immediately after routine performance and fingertip blood samples were taken after 3min for the measurement of blood lactate concentration. Heart rate measurements were continuously recorded during performance (Polar Sport Tester) and each athlete performed four to eight routines on the same nova analysis and post-hoc Scheffe. Results: Elite-athletes presented higher VO values at the maximum effort and the various apparatus (rope p<.01, hoop p<.05, ball p<.01, clubs p<.05) as comparing with sub-elite athletes (Fig 1), ribbon routines (p>.05). Heart-rate and lactate values were similar between elite and sub-elite gymnasts (p>.05) except for rope (p<.05) (Fig 2). The blood lactate values revealed individual variations in different apparatus. Also, no significant differences were observed on HR and La in each level separately during the RG routines on different apparatus. In addition, the heart rate response gave high values indicating the high intensity and the requirements of energy demands in all routines. Discussion: The results of the present study indicate that elite athletes possess higher VO2max than sub-elite gymnasts and both of them use even higher values during RG routines (Fig 1). This reveals the importance of oxygen consumption in the performance of RG athletes in order to attain successful routines. Elite athletes not only possess, but also use more energy during RG routines, because of the high demands and the complexity of various movements requiring at this competitive level. The HR and La values, however, appear to be similar between elite and sub-elite athletes as well as among the five apparatus (rope, hoop, ball, clubs, ribbon) despite the level of athletes and the material regulations of different apparatus.